Sundays are blue: aren't they? ; the day-of-the-week effect on subjective well-being and socio-economic status - Alpaslan Akay; Peter Martinsson (Institute for the Study of Labor (IZA), 2009)
This paper analyses whether individuals are influenced by the day of the week when reporting subjective well-being. By using a large panel data set and controlling for observed and unobserved individual characteristics, we find a large day-of the-week effect. Overall, we find a 'blue' Sunday effect with the lowest level of subjective well-being. The day-of-the-week effect differs with certain socio-economic and demographic factors such as employment, marital status and age. The paper concludes with recommendations for future analyses of subjective well-being data and design of data collections.
Keywords: C23; D60; I31; 330; Subjective well-being; day-of-the-week effect; Lebenszufriedenheit; Lebensqualität; Sozialer Status; Zeit; Panel; Schätzung; Deutschland